Budaya “Pakewuh” Santri pada Kyai: Relevansi Budaya Pendidikan Pesantren Terhadap Tantangan Dunia Islam di Era Globalisasi - M Baiqun Isbahi; Novy Setia Yunas (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
The phenomenon of communication process in pesantren occurs among kyai, ustadz, and santri creating a distinctive educational culture among pesantren. The relationship among them is very close, because santri permanently live in a pesantren environment nearby the kyai’s house. Europe in the mid-century is full of power, doctrine and domination of the church which has purpose to guide people towards a righteous life, but on the other hand the dominance of this church without thinking of the dignity and freedom of human beings who have feelings, thoughts, desires and ideals to determine his own future, therefore the development of science is inhibited. Meanwhile, the culture of education in pesantren raises a similar similarity though not the same, where the position of kyai is considered as the representative of the god who escaped the error. Both of these phenomena are presenting the dominance of the religious doctrine that can penetrate the layers of public confidence in various areas of life. Based on the study, it can be concluded that the leadership in pesantren with the